Estudios fenológicos en los hayedos del sistema ibérico - Tarazona T.; Moreiro S.; Zaldivar P.; Calvo R. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
A phenological study in beech forests was made in the Demanda mountains (Sistema ibérico, Spain). It carries out the knowledge of the relationship between climatic variations in this region with altitude and other ecological factors. These relationships are reflected in the phonological map. The second part of this study deals with the influence of temperature on the sprouting of Fagus sciatica L.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)